PENGARUH PENERAPAN BAHAN AJAR BERMUATAN NILAI NILAI KARAKTER DALAM MODEL PEMBELAJARAN LANGSUNG TERHADAP HASIL BELAJAR SISWA KELAS XI SMAN 1 BUKITTINGGI - Bahril Ilmiwan (PILLAR OF PHYSICS EDUCATION, 2013)
The purpose of this research is to know the influence of the application of teaching material contains character values in direct instruction model against the results of learning to grade XI SMAN 1 Bukittinggi. This research included in this type of research experiments with type quasy experiment research using randomized control study design group posttest only design. The population of the research was the students of class XI SMAN 1 Bukittinggi. Samples were taken using a purposive sampling technique, which consists of XI IPA 1 as experimental class with the number of 35 students and XI IPA 3 as the control class with the number of 35 students. Data analysis techniques using a t-test on the level of significance of 0.05 for the domain of  cognitive, affective, and psychomotor. Data collection techniques in the form of a written test to the domain of    cognitive and affective domain for observation and psychomotor. The results showed that the average value of experimental class higher than the class of the control. Thus, application of teaching material values-laden characters effect on student learning outcomes at the level of significance of 0.05. Keyword : Teaching Material, Character Values, Direct Instruction Model